Funk brasileiro e os embates políticos de gênero o protagonismo feminino em queståo - Miranda, Michele Gomes (2022)
The theme of this dissertation is Brazilian funk, with a specific focus on the gender problems that have been tacitly fed during the strengthening of this market. The ostensible presence of communicational capitalism is noted in the way the music industry operates and, from its specific actions in the funk market, axes of protagonism are created that trigger numerous problems related to the performance of women. Since 2016, Funk has grown by 4,694% on the leading global streaming platform, Spotify. In addition, the channel of funk producer KondZilla became the third largest in the world, surpassing global phenomena such as Justin Bieber and Ed Sheeran. However, gender equality has not kept pace with this growth. The proportion of women in Brazilian funk, with a leading role in the rhythm created in the favelas of Rio de Janeiro in the 1980s, is still exceedingly insignificant compared to the number of male MCs and DJs. The main question of this research is to ask if in funk the woman is where she wants and what kind of debates are being conducted by the protagonists of the new scenes that are presented